Tripled coincidence points for weakly compatible and its variants in fuzzy metric spaces (JOURNAL OF ADVANCES IN MATHEMATICS, 2015)
In this paper, we will introduce the concept of weakly commuting and variants of weakly commuting mappings (R-weakly commuting, R-weakly commuting of type (Af), type (Ag), type (P) mappings) for triplet in fuzzy metric spaces. Secondly, we introduce the notion of weakly compatibility and its variants weakly f-compatible maps and weakly g-compatible maps. At the end, we prove common ï¬xed point theorems for a pair of weakly compatible map and their variants, which generalize the results of various authors present in ï¬xed point theory literature. Our result is validated with a suitable example.